PENGARUH RASIO LIKUIDITAS, SOLVABILITAS DAN AKTIVITAS TERHADAP KINERJA KEUANGAN MENGGUNAKAN VARIABEL INTERVENING CSR (STUDI PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2014-2018) - Santi Widyaningrum; Vincent Hendrawan (Parsimonia - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of liquidity ratios, solvency and activities on financial performance with Corporate Social Responsibility (CSR) as an intervening variable. This type of research is explanatory research. The population in this study were 16 companies listed on the Indonesia Stock Exchange for the food and beverage sub-sector for the period 2014-2018 with a total sample of 13 companies obtained through the purposive sampling method. The data analysis technique used in this study is path analysis. The results show that the liquidity ratio (current ratio) has a positive effect on financial performance (return on assets) while the solvency ratio (debt to equity ratio) has a negative effect on profitability (Return on Assets) and the Activity Ratio (Total Assets Turnover) has a positive effect on performance. finance (Return on Assets). The intervening variable Corporate Social Responsibility (CSR) is able to affect the liquidity ratio (Current Ratio), solvency (Debt to Equity Ratio) and Activity Ratio (Total Assets Turnover) to financial performance (Return on Assets) in 13 manufacturing companies in the food and beverage sub-sector which listed on the IDX for the period 2014-2018.